2013
DOI: 10.1558/genl.v7i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Talking at cross-purposes?

Abstract: Following decades of feminist linguistic activism, and as a result of a greater awareness of the vital role that non-sexist language plays in achieving social equality, different campaigns were launched in many countries leading to a more frequent use of so-called inclusive language. Bringing this together with current theoretical approaches to translation studies which have been defining translation as an ideological act of intercultural mediation since the 1990’s, this article seeks to examine to what extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As Leonardi and Taronna (2011) and Castro (2013) argue, prefacing and footnoting is not exclusively a feminist translation procedure; this procedure is employed in translated works that do not foreground gender. The only practice that is considered to be essentially feminist is hijacking, the appropriation of a text whose intentions are not necessarily feminist by the feminist translator.…”
Section: Resultsmentioning
confidence: 99%
“…As Leonardi and Taronna (2011) and Castro (2013) argue, prefacing and footnoting is not exclusively a feminist translation procedure; this procedure is employed in translated works that do not foreground gender. The only practice that is considered to be essentially feminist is hijacking, the appropriation of a text whose intentions are not necessarily feminist by the feminist translator.…”
Section: Resultsmentioning
confidence: 99%
“…the marginal use of inclusive language in professional translation, which is indeed a complex issue. This has been explored, amongst others, by Castro (2013), who has analysed "the ideological, poetic and economic pressures that (still) define the professional practice of translation". She has examined "the gap between the theory and practice of translation", and pointed at "a possible 'missing link' between feminist approaches to linguistics and to translation studies" (p. 35).…”
Section: Analysis Of the Translationsmentioning
confidence: 99%
“…She has examined "the gap between the theory and practice of translation", and pointed at "a possible 'missing link' between feminist approaches to linguistics and to translation studies" (p. 35). That is, the feminist proposals to avoid sexism in language have not been applied in professional translation, as Castro (2013) and Bengoechea (2014) have shown. By the same token, we have identified a missing link between the research done in Translation Studies and its pedagogic implications.…”
Section: Analysis Of the Translationsmentioning
confidence: 99%
“…Reimóndez's article also contains several statements that the publisher sent to the media. Concerning this same case, I would also like to recommend two articles by the academic Olga Castro (2009Castro ( , 2013 published in the journals Quaderns ( 2009) and Gender and Language (2013). Apart from examining the power imbalance in the relationship between translation and para-translation, Castro analyzes the choices and decisions made in two translations of Mark Haddon's novel: the one registered with María Reimóndez's copyright and the one finally published by Rinoceronte and signed by Moisés R. Barcia, who is both a translator and the person in charge of the publishing house Rinoceronte.…”
Section: Galicia: Feminist Translation and The Patriarchal Nationmentioning
confidence: 99%
“…Meaning is actually generated through complex social conventions, not on one individual's initiative. Olga Castro (2013) has also suggested that "collaboration with the author is an option, but should not be seen as an imperative" (p. 50). The publisher, Moisés R. Barcia, and the translator, María Reimóndez, could not eventually reach an agreement and the former canceled the contract, did not pay the translator for her work and published a translation under his own name (Haddon 2008).…”
Section: Galicia: Feminist Translation and The Patriarchal Nationmentioning
confidence: 99%